The cardiac toxicity of radiotherapy – a review of characteristics, mechanisms, diagnosis, and prevention. (3rd October 2021) - Wei, Tianhui; Cheng, Yufeng
Abstract: Purpose: Radiation-induced heart disease (RIHD) is one of the most serious complications of radiotherapy. The purpose of this paper is to review recent researches about cardiac toxicity of radiotherapy in clinical characteristics, mechanisms, diagnosis, and prevention. Conclusions: Powered by the rapid development of medicine, the overall survival (OS) of cancer has been improved significantly. Surgery, chemotherapy, and radiotherapy (RT) are three critical ways in the comprehensive treatments of cancer. There is a consensus that early diagnosis and interventions for the prevention of RIHD are crucial. This review concludes recent clinical and experimental studies on RIHD. RIHD, a heterogeneous and serious disease, is a spectrum of heart disease including myocardial disease, pericarditis, coronary artery disease, valvular heart disease, and conduction system dysfunction. Mean heart dose, biomarkers, and detecting techniques are important components in detecting heart injury. Improvements in radiotherapy regimens remain the primary goal of prevention. Further investigation is needed beyond the observation period of most of these studies.